Detection and Classification of Obstacles for Autonomous Vessels Using Machine Learning - António Pedro Rodrigues Pereira (2019)
Development of a system capable of obstacle detection and classification of various types that may be subject of collisions and result in damages to the ship or even its own total loss. The system is also capable of detection the horizon line, to estimate the relative distance of the detected objects to the vehicle current position. This is achieved throught Deep Learning techniques, namely by the use of Convolutional Neural Networks.